Examining the Impact of Scarcity Perception, Visual Appeal, and Fear of Missing Out on Impulse Buying: A Case Study of Blindbox-Popmart Consumers at Beachwalk Bali - Putu Ayu Trisna Febrianty; Ni Putu Dera Yanthi; Nyoman Dewi Pitaloka Cahyadi (Universitas Veteran Bangun Nusantara, 2025)
Blind boxes have become a rapidly growing trend among teenagers due to their primary appeal, which lies in the excitement of “unboxing,” the chance of obtaining rare items, and the emotional experience offered through attractive packaging. This study aims to examine the influence of scarcity perception, visual appeal, and fear of missing out (FOMO) on impulse buying. The research employs a quantitative approach using a survey method with a questionnaire distributed to 200 respondents who buy Blindbox PopMart in Beachwalk Bali. The sampling technique used is purposive sampling with specific criteria. Data analysis was conducted using the Multiple Linear Regression Model with SPSS to test the relationship between the independent variables and the dependent variable. The results indicate that scarcity perception has a positive and significant effect on impulse buying, visual appeal has a positive and significant effect on impulse buying, and fear of missing out also has a positive and significant effect on impulse buying. The findings are expected to be applied by companies in the marketing field to create a sense of scarcity, enhance the visual design appeal of products, and leverage existing trends to boost sales and contribute to the enrichment of the academic literature on consumer behavior.